The Effects of Aging and Time of Day on Inhibitory Control: An Event-Related Potential Study - Rabi, Rahel; Chow, Ricky; Paracha, Shahier; Hasher, Lynn; Gardner, Sandra; Anderson, Nicole D.; Alain, Claude (Frontiers in Aging Neuroscience, 2022)
Time of day (TOD) influences on executive functions have been widely reported, with greater efficiency demonstrated at optimal relative to non-optimal TOD according to one’s chronotype (i.e., synchrony effect). Older adults (OAs) show declines in inhibitory control and are more sensitive to the effects of circadian variation on executive functioning. To date, no studies have investigated the effects of TOD and aging on executive functioning using electrophysiological measures. The present study investigated the effects of aging and TOD on the neural correlates of inhibitory processing (N2 and P3) using event-related potentials (ERPs). Go-NoGo and Flanker tasks were administered to 52 OAs of morning chronotype and 51 younger adults (YAs) of afternoon-to-evening chronotype who were randomly assigned to morning or afternoon test sessions, with the optimal TOD for OAs in the morning and for YAs in the afternoon/evening. While behavioural results demonstrated no TOD effects, ERPs indicated synchrony effects. Both YAs and OAs showed greater modulation of Go-NoGo N2 and greater P3 amplitude during the non-optimal than optimal TOD, consistent with the synchrony effect. For the Flanker task, age differences in P3 amplitude were only apparent during the non-optimal TOD. These results suggest that processes associated with inhibitory control are differentially affected by TOD and aging, with age-related reductions in inhibitory efficiency during off-peak test times on measures of interference control. These findings highlight the sensitivity of ERP to detect TOD effects in the absence of behavioural differences, confirm more pronounced TOD effects in OAs relative to YAs on ERP measures of interference control, and reinforce the need to assess and control for circadian typology in research studies.